High-resolution two-dimensional mapping of arsenic concentration in soil-water micro-interfaces with diffusive gradients in thin films - Xitong Li; Jiahui Zuo; Chuangchuang Zhang; Tieliang Zhang; Zeying He; Qiwen Zhou; Yujie Zhao; Wenjng Liu (Environmental Chemistry and Ecotoxicology)
Arsenic (As) contamination in soils poses significant environmental and health risks, particularly in Asia. We present a new diffusive Gradients in thin-film (DGT) binding material (Bio-TiO2) using microbial-assisted in situ precipitation, to determine the spatial distribution of As at submillimeter resolution. The Bio-TiO₂ gel exhibited superior homogeneity, smaller particle sizes, and higher adsorption capacity for As(V) (133.6 μg/cm2) and As(III) (55.2 μg/cm2) compared to most reported As binding gels. The DGT measurements provided high-resolution, two-dimensional mapping on As distribution in soil-water micro-interfaces process during soil flooding and drainage conditions, elucidating As dynamics with a sub-millimeter resolution (∼0.1 mm per pixel). This work presents an innovative and efficient method for As monitoring, providing significant implications for assessing As bioavailability and environmental risk.